The Necessity of Interdisciplinary Investigations for Proper Understanding of the History of International Law - Fernando, Inura (Victoria University of Wellington Law Review, 2021)
The heroic notion of international law as a distinct discipline is often challenged by interdisciplinary scholarship, particularly by those who are committed to highlighting the legacy of colonialism on colonised peoples. This article will highlight the entrenched formalism in international law histories. This article laments ways in which orthodox work fails to canvass histories beyond the text of the covenants and treaties that constitute international law. This article will examine key examples that highlight the importance of individual actors and sociological concepts in framing historical issues. These examples show how interdisciplinary investigations allow for a holistic understanding of the nature of international law histories. In doing so, this article aims to provide a pathway to negate the direct and indirect censorial effects of a discipline such as international law on the rendering of international law histories.